Enhanced tensile performance of epoxy and E-glass/epoxy composites by randomly-oriented amino-functionalized MWCNTs at low contents. (March 2015) - Rahman, Muhammad M; Hosur, Mahesh; Zainuddin, Shaik; Jahan, Nusrat; Miller-Smith, Everett B; Jeelani, Shaik
Effect of amino-functionalized multi-walled carbon nanotubes (NH2 -MWCNTs) on the tensile performance of epoxy and E-glass/epoxy composites was investigated. Low weight percentages (0.3 and 0.4 wt%) of NH2 -MWCNTs were dispersed into a DGEBA epoxy resin using combination of sonication and three-roll milling methods. Composites with plain weave E-glass fabrics were fabricated by compression molding process. Tensile test results showed a significant enhancement in strength, modulus and toughness of epoxy and E-glass/epoxy composites at 0.3 wt% loading of NH2 -MWCNTs. Micrographs of NH2 -MWCNTs-incorporated epoxy and E-glass/epoxy composites revealed better dispersion of nanotubes in epoxy, better bonding between nanotubes and polymer and improved interfacial adhesion between fiber/matrix at 0.3 wt% loading. Micromechanical models were used to predict the tensile properties and compared with the experimental results. An improved dispersion and hence an enhanced crosslink interaction between NH2 -MWCNTs and epoxy lead to the improvements in the tensile properties of the epoxy nanocomposites close to predicted values at 0.3 wt% loading. A similar rationale applies for the increase in properties of E-glass/epoxy nanocomposites.